P176 A case of lupus enteritis successfully treated with anti-TNF alpha inhibitor. (23rd March 2020) - Bilia, Silvia; Giannini, Daiana; Giannese, Domenico; Mumolo, Gloria; Capecchi, Riccardo; Ceccarelli, Linda; Migliorini, Paola; Tavoni, Antonio
Abstract : Background: Gastro-intestinal manifestations in systemic lupus erythematosus (SLE) can affect up to 40% of patients, including enteritis presenting as mesenteric vasculitis, pseudo-obstruction or protein-losing enteropathy. We present a case of lupus enteritis successfully treated with anti-TNFalpha inhibitor. Methods: A 28-year-old woman was evaluated for diarrhea, abdominal pain, fever and rectal bleeding not responsive to antibiotics. She had a thirteen-year history of SLE in remission with Mycophenolate Mofetil and previous muco-cutaneous and haematologic relapses, myocarditis and end-stage renal disease (IV-class glomerulonephritis). She previously underwent multiple immunosuppressants including ciclophosphamide, cyclosporine, anti-CD20, immunoglobulins. One month before the onset of symptoms she discontinued MMF for worsening anemia. Simultaneously we reported signs of lupic flare (low C3, haemolytic anemia, lymphopenia, fever, arthralgias and malar rash). Pulse-steroids and IVIg followed by cyclosporine were initially performed with only temporary benefit. Enteric CT-scan and endoscopy revealed chronic and acute colo–rectal and gastric inflammation (cryptitis, erosions, necrosis, microgranulomas). Anti-TNFalpha inhibitor Infliximab (5 mg/kg) was added to Azathioprine 50 mg/daily. Within a month we observed clinical and serological sustained remission. Results: Typically, mesenteric vasculitis involves small arteries or venules. Histological examination reveals submucosal and muscular layers infiltration and necrotizing vasculitis, with panmural predominant eosinophilic, neutrophilic or mixed infiltrate. The distinction of inflammatory bowel disease (IBD) from enteric-SLE can be challenging. In this case, an early anti-flogistic therapy may have led to uncomplete microscopic patterns not fullfilling criteria neither for enteric vasculitis nor IBD. A lupic flare with predominant gastro-enteric presentation is the most plausible hypothesis because of the infrequent association between SLE and IBD and simultaneous extra-intestinal lupic features. Abdominal involvement in a patient previously treated with high dosage cyclophosphamide (10 g) and the lack of response to azathioprine lead to the introduction of anti-TNFalpha inhibitor. Conclusion: The role of TNFalpha in SLE is controversial and TNFalpha inhibitors are reported to control SLE-arthritis. Further studies are needed to evaluate their role in the management of gastro-enteric SLE.